2021
DOI: 10.3389/fneur.2021.744118
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Neurological Complications in Adults With Sickle Cell Disease: A Retrospective Cohort Study

Abstract: Introduction: Risk factors for neurological complications in sickle cell disease differ in the adult and pediatric populations. Here, we focused on neurological complications in adults with sickle cell disease.Methods: Patients were selected using the audit data from the St George's Hospital Red Cell Database. The genotyping, demographics, clinical data, and investigation findings were collected.Results: A total of 303 patients were enrolled in the study: hemoglobin S homozygosity (HbSS) genotype 56%, hemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In a recent comprehensive review, Sahu et al reported mainly dysexecutive disorders with learning difficulties, working memory disorders and attentional disorders in adults and children, with dramatic consequences both in their daily and professional lives, but also in terms of therapeutic follow-up. Cognitive disorders are more important in patients with cerebro-vascular disorders like stroke and/or SCI or vasculopathy [ 11 , 12 ]. However, cognitive disorders were depicted in adult patients with SCD, even in the absence of overt neurological events, in a neuroimaging study [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent comprehensive review, Sahu et al reported mainly dysexecutive disorders with learning difficulties, working memory disorders and attentional disorders in adults and children, with dramatic consequences both in their daily and professional lives, but also in terms of therapeutic follow-up. Cognitive disorders are more important in patients with cerebro-vascular disorders like stroke and/or SCI or vasculopathy [ 11 , 12 ]. However, cognitive disorders were depicted in adult patients with SCD, even in the absence of overt neurological events, in a neuroimaging study [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the longitudinal Cooperative Study of SCD, the estimated prevalence of stroke was 11% by age 19 years and 24% by age 45 years, with the highest risk and lowest age at first stroke among people with homozygous hemoglobin S (HbSS) disease and hemoglobin Sβ 0 (HbSβ 0 ) thalassemia. 21 Stroke risk is lower among people with hemoglobin SC (HbSC) disease 21 , 22 Hemoglobin Sβ + (HbSβ + ) thalassemia and other compound heterozygous forms of SCD have variable stroke risk, which may be related to degree of anemia and hemolysis. 23 …”
Section: Introductionmentioning
confidence: 99%
“…In the longitudinal Cooperative Study of SCD, the estimated prevalence of stroke was 11% by age 19 years and 24% by age 45 years, with the highest risk and lowest age at first stroke among people with homozygous hemoglobin S (HbSS) disease and hemoglobin Sβ 0 (HbSβ 0 ) thalassemia. 21 Stroke risk is lower among people with hemoglobin SC (HbSC) disease 21,22 Hemoglobin Sβ + (HbSβ + ) thalassemia and other compound heterozygous forms of SCD have variable stroke risk, which may be related to degree of anemia and hemolysis. 23 Strokes in people with SCD frequently involve the distributions of median cerebral arteries, due to chronic narrowing of the internal carotid arteries, but strokes can also involve the vertebrobasilar arteries and other vessels along the Circle of Willis, potentially in association with vascular anomalies like moyamoya syndrome.…”
Section: Introductionmentioning
confidence: 99%